ChemInform Abstract: The Borosulfates K4[BS4O15(OH)], Ba[B2S3O13], and Gd2[B2S6O24]. Issue 23 (19th May 2016) - Gross, Peter; Kirchhain, Arno; Hoeppe, Henning A.
Abstract: K4 [BS4 O15 (OH)] (I) is prepared by heating a 1:2 molar mixture of HBO2 and K2 S2 O7 (glass ampoule, 300 °C, 60 h).